STEM-critical thinking skills of natural science students in Kurikulum Merdeka - Utary, Novitria; Anwar, Yenny (Universitas Negeri Padang, 2023)
Education has entered a new era following the Covid-19 pandemic. The government has implemented a new curriculum, called the